Top Marks Donna Krohn talks to Bruce Marks from the Boston Ballet - Krohn, Donna (Dance Books Ltd., Alton,Hampshire (UK), 1998)
Bruce Marks made a successful transition from dancer to artistic director. He talks to Donna Kronh about his years at the helm of the Boston Ballet. PALABRAS CLAVE: Bruce Marks, Boston Ballet, career.